Tindik Area Oral di Kalangan Mahasiswa - Hayatun Safrina; Dewi Nurul Mustaqimah; Herry Novrinda (Faculty of Dentistry, Universitas Indonesia, 2015)
Body piercing has been practiced universally as far back as can be traced, and now has been admitted by teens and undergraduate students. Oral complications of oral jewelry, especially tongue piercing, have been well documented, e.g. Ludwig's Angina and bifid tongue. This study was done to explore the impact of oral piercing among students. For this purpose, 32 students with oral piercing in Jakarta were asked to fill in a questionnaire form after having had intraoral piercing for less than one year. It was concluded that the subjects did not sufficiently understand the dangers of piercing. Medical and dental professionals should warn patients with piercing about potential dangers posed by this current fashion.